THE IMPACT OF THE RUSSIAN-UKRAINIAN CRISIS ON EUROPEAN SUPPLY OF PRECIOUS METALS - Ivana Sedinić; Helena Nikolić (Poslovna Izvrsnost, 2023)
The paper deals with the issue of the last global crisis caused by the Russian aggression against Ukraine and the disruptions it caused on the precious metals market. A global imbalance was caused accompanied by significant disruptions in the supply chains and inflation. Additionally, the consequences of such an event will be felt for many years even after the end of the war. Considering the fact that production of Russia and its export are crucial for the supply of the European market, special emphasizes has been placed on Europe. Through the work, a detailed analysis of the previous import of precious metals into the selected European countries was made, fluctuations in the prices of precious metals were analysed, as well as the reasons for price fluctuations. Also, projections of compensation plans for Russian imports, as the main distributor so far, are presented, along with projections of further price movements. The aforementioned war pointed to a series of failures in the organization and structure of business in European countries, which were forced to restructure after many years of inertia and inactivity. This is the crucial strategic way if they want to survive the crisis caused by the war. Certainly, in the most ungrateful position are the countries whose most important industries are largely dependent on the import of precious metals. Nevertheless, the projections are positive, and it is estimated that Europe should get out of the crisis in the short term with proper investments and carefully planned strategies.